Survei Kondisi Kebugaran Wasit Futsal Sukabumi Tahun 2019 - Anra Wiono; Ahmad Alwi Nurudin; Firman Maulana (Jurnal Syntax Transformation, 2020)
The purpose of this study was to determine the fitness conditions of the 2019 Sukabumi futsal referee using quantitative methods and data collection techniques carried out by a survey method of the physical fitness conditions of the Sukabumi futsal referees in 2019. The survey method was used to get from certain natural places (not made for) however this research does data collection, for example, distributing questionnaires, conducting tests and interviewing in a structured manner (the treatment is not the same as the experiment). The study was conducted to review the physical fitness condition of Sukabumi futsal referees in 2019. The results of the analysis showed that referees whose cardiorespiration freshness were classified as very poor were 2 people or with a percentage of (6.7%) less classifications of 3 people (10%) , the classification is quite good a number of 16 people (53.3%), a good classification of 3 people (10%), and a very good classification of 6 people (20%). From the above data it can be concluded that the referee level of Sukabumi City and Regency referee is in the quite good category.